Evaluación técnica de la cadena de frío en la producción de carne Bovina en Colombia, para ACAIRE (2018)
The technical evaluation of the cold chain in beef production in Colombia is a project that deserves attention; In this work the percentage of compliance of the processes, environments and equipment of the different links that make it up was qualified, with respect to what is dictated by the national regulations. A diagnosis was made of the regulations that indicate how each one of the processes and how they should be the environments of each of the links corresponding to that chain. The evaluation of the environments in which the meat is handled, stored and marketed, the temperature measurement in the refrigeration equipment involved and the characterization of thermal loads were carried out, these activities were achieved with a series of visits to the different places that make up the links of the cold chain; subsequently the calculations of the design parameters according to national regulations were carried out. With the results obtained, the evaluation of the processes, performance and infrastructure of cold chain environments and equipment in the production of bovine meat was developed, calculating the averages and verifying the percentage of compliance that this has in Colombia. Finally, the environmental impact analysis was made taking into account the processes and equipment involved in each of the links of the cold chain and the evaluation of the total cost of the Project.